Konstruktion av lindningsmaskin - Arvidsson, Johan; Penndal, Jesper (My University, 2021)
The report is a compilation of the results that emerged during the development of a new winding machine for winding grip tape on floorball sticks. The work was carried out in cooperation with the brand Jolly, which belongs to Habo Plast AB. The goal for Habo Plast is to increase sales of Jolly's floorball sticks and thereby also develop a new and time-efficient production line. The machine used today for wrapping floorball sticks has deficiencies and a new machine needs to be designed to be well suited with the new production line. The work started with a thorough analysis of the existing machine, which generated an understanding of which requirements are needed for the new machine. With the results from this analysis, several concepts could be generated, and a final concept was constructed. The chosen concept largely consists of standard components, as well as some unique details that have been developed during the development process. The concept works by manually fixate the club shaft in the machine. The club shaft is connected to an electric motor, which enables a rotation of the club shaft. After the club shaft is fixed in the machine, the operator is required to manually wrap the knob of the floorball shaft with the grip tape. The grip tape is then attached to a tape holder which ensures that the grip tape is applied to the floorball stick with a specific tensile force and a pitch angle. When the grip tape is clamped in the machine, the winding process takes place automatically thanks to the tape holder being connected to a drive belt driven by an electric motor. When the club shaft has rotated a specific number of rotations, the machine comes to a halt and the winding process is completed. The constructed concept wraps floorball sticks more time-efficiently and with higher quality. It will also be safer for the operator to wrap floorball sticks with the chosen concept. The final concept has been visualized with a CAD-model and further development is required before the machine can be manufactured and assembled.